Seminar Manajemen Stress Pada Pendeta GBKP Klasis Kabanjahe Sukarame - Brahmana, Karina Meriem Beru (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The Stress Management Seminar for Pastors at GBKP Klasis Kabanjahe Sukarame was organized in response to the heavy duties and responsibilities borne by pastors. As leaders, shepherds, and teachers, pastors often face complex and demanding service challenges. They must provide maximum service to the congregation, frequently encountering dilemmas between prioritizing family interests or those of the congregation. This situation potentially leads to significant physical, psychological, and emotional fatigue, ultimately resulting in stress. The seminar aimed to equip pastors with stress management knowledge and skills to better handle the pressures encountered in their daily duties. Through an interactive and practical approach, the seminar covered stress management techniques, including relaxation strategies, time management, and the development of social support systems. The results of the seminar indicated a significant benefit for the pastors in terms of reduced stress levels and improved overall well-being. It is hoped that this seminar can serve as a model for similar future activities, supporting the mental and emotional health of pastors in their service duties. Kata Kunci: stress management, coping strategies, priest